Leveraging Asynchronous Online Learning to Deliver Intercultural Learning Outcomes in an EAP Program: Lessons for Future Practice - Michael Henry Landry (BC TEAL Journal)
Having the intercultural communication skills required to navigate diverse communities is imperative, especially for international students. English for academic purposes (EAP) programs are one support offered in a wide range of contexts across post-secondary institutions in Canada to help students use English as an additional language (EAL) with their socialization into their new communities. However, there has been a lacuna in the research regarding how to meaningfully deliver intercultural communication outcomes in crowded EAP curricula. Drawing on a theoretical framework involving literature on EAP in Canada, additional language socialization, and intercultural communicative competence, this qualitative study presented the pedagogical strategies and implications of using online asynchronous intercultural learning outcomes in an EAP program in British Columbia, Canada. Data were generated from online questionnaires, student e-portfolios, focus groups, and individual interviews with students and graduate teaching assistant participants. Identified meaningful units of text in the data were coded, and the codes were gathered together into overarching and supporting themes. The findings point to the benefits of leveraging online platforms to find space for intercultural learning outcomes in EAP and key imperatives for delivery.